STUDI RUMAH TANGGA PENGRAJIN BATU LADO DI KOTO PANJANG KELURAHAN LIMAU MANIS KACAMATAN PAUH KOTA PADANG - -, Delvinaliza - (Pendidikan Geografi, 2014)
This study aimed to obtain information and data on (1) Level of Household Welfare Lado Custom Stone Koto Panjang Village Limau Manis Padang Pauh subdistrict is viewed in terms of a childs education craftsmen (2)) Level Household Welfare Lado Custom Stone Koto Panjang Limau Manis kelurahan Padang Pauh subdistrict is viewed in terms of revenue craftsmen (3)) Level Household Welfare Lado Custom Stone Koto Panjang Village Limau Manis Padang Pauh subdistrict is viewed in terms of Number of Family Members artisans (4) Level of Household Welfare craftsmen stone Lado in Koto Panjang Village Sweet Lemons Padang Pauh subdistrict is viewed in terms of Meeting the Needs Family craftsmen.This research type is descriptive, the population in this study is that Lado stone craftsmen are in Koto Panjang keluarahan Sweet Lemons. Samples were taken through the region of total sampling methods ie people who work as stone craftsmen in Koto Panjang Village Lado Sweet Lemons Padang Pauh subdistrict. The sample taken total sampling of 65 respondents.The results of this study found: 1) In general, the education of children of craftsmen Stone Lado classified as moderate as most of their children graduated from high school (29.23%). 2) the average income artisans in 1 month> Rp 1.000.000 - Rp 3,000,000 (35.39%). 3) The number of family members craftsman 5 (36.923%) and dependents in the family> 5 people (46.154%). 4) ability to meet the needs of a family of craftsmen are able to meet the needs for food and clothing (49.231%).